2010
DOI: 10.4103/0301-4738.62656
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic adenoma of a subconjunctival ectopic lacrimal gland

Abstract: This report describes a case of pleomorphic adenoma of an ectopic lacrimal gland arising subconjunctivally in the lateral fornix in a 13-year-old girl. The tumor was removed surgically in toto with the capsule. This is probably the first reported case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…5 It has also been described in the eyelid, conjunctiva, sclera, cornea, iris, choroid, and orbit. 6 It can present either as an isolated choristoma, or as a complex choristoma also containing cartilage, nerve, or be located within a dermolipoma, as was found in the described case. 5 Like a dermolipoma, ectopic lacrimal gland tissue tends to occur deep in the superotemporal conjunctiva, and is thought to be aberrantly located palpebral lacrimal gland tissue from the adjacent lacrimal fossa.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…5 It has also been described in the eyelid, conjunctiva, sclera, cornea, iris, choroid, and orbit. 6 It can present either as an isolated choristoma, or as a complex choristoma also containing cartilage, nerve, or be located within a dermolipoma, as was found in the described case. 5 Like a dermolipoma, ectopic lacrimal gland tissue tends to occur deep in the superotemporal conjunctiva, and is thought to be aberrantly located palpebral lacrimal gland tissue from the adjacent lacrimal fossa.…”
Section: Discussionmentioning
confidence: 74%
“…5 Like a dermolipoma, ectopic lacrimal gland tissue tends to occur deep in the superotemporal conjunctiva, and is thought to be aberrantly located palpebral lacrimal gland tissue from the adjacent lacrimal fossa. 6 Alyahya et al 5 reported the largest series of ectopic lacrimal gland describing 61 such cases. In their study, they found that most cases (38, 62%) were complex choristomas, while 23 cases (38%) represented isolated ectopic lacrimal gland tissue.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, reports in the literature describe ectopic lacrimal glandular tissue (Dallachy 1961;Solaroglu et al 2005). Such ectopic lacrimal gland tissue, though very rare, may also harbour a tumour (Patyal et al 2010;Alsuhaibani 2012;Obi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Pleomorphic adenomas of the orbit can be found in the lacrimal gland, in the palpebral lobe of the lacrimal gland which is associated with a raised intraocular pressure, in the upper lid, in the lower lid developing in Krause's gland, in the lacrimal sac and in the orbit [3].…”
Section: Discussionmentioning
confidence: 99%
“…Pleomorphic adenoma is the most common epithelial tumour of the lacrimal gland, which represents 12% of all the lacrimal fossa lesions [1]. It typically presents in middle age and is rare in children who are under the age of 16 years, with only a few previously reported cases [2][3][4][5][6][7]. We are reporting a case of a lacrimal gland pleomorphic adenoma in a 11 year old girl.…”
Section: Introductionmentioning
confidence: 99%